Hemosiderin: a new marker for sentinel lymph node identification - Pinheiro,Luiz Gonzaga Porto (2009)
PURPOSE: To evaluate and present our initial results of a new marker (hemosiderin) for mammary sentinel lymph node identification in an experimental model. METHODS: Skins mapped like a lymphatic duct draining to the axilla in patients submitted to breast biopsy, in our mastology service, stimulated us to try it in an animal model (female dogs). Our theory was that some blood derivate (hemosiderin) was captured by macrophages and accessed the lymphatic ducts in direction to the axilla. Six female dogs of no defined race were studied. We injected 0,2 ml of technetium on both superior mammary glands. After ten minutes, a 2,5 ml solution of hemolized blood (hemosiderin) from the own animal was injected in the subareolar lymphatic plexus on the left superior mammary gland and 2,5 ml of patent blue concomitantly and equally on the contralateral gland. Ten minutes after, incisions on both axilas were made to search, through the lymphatic mapping and a gamma probe, the sentinel lymph nodes. RESULTS: Seven brown sentinel lymph nodes were indentified and also radiomarked on the left axilla. Six blue sentinel lymph nodes were identified and also radiomarked on the right axilla. CONCLUSION: Preliminary studies of a potential new dye for sentinel lymph node identification are presented. It may be the change of the current use of the blue dyes and their severe side-effects on patients submitted to sentinel lymph node biopsies.